Peningkatan Literasi Keuangan Rumah Tangga sebagai Upaya Peningkatan Kesejahteraaan Masyarakat Desa Balesari, Kecamatan Ngajum, Kabupaten Malang - Firmansyah, Rizky; Restuningdiah, Nurika; Arzaq, Ach. Littausil; Muhammad (Pendidikan Matematika, FKIP Universitas Mataram, 2023)
Balesari Village is a village with a good potential for natural resources such as agriculture and tourism. However, the majority of the people in Balesari Village still do not have a good level of financial literacy. Therefore, the community service team initiated efforts to improve financial literacy by presenting materials by experts and applying theories according to the conditions of Balesari Village. The results of the community service in Balesari Village include an increase in the community's knowledge of household financial literacy, an improvement in the community's ability to manage finances up to long-term financial planning, and an increase in enthusiasm for further learning about household financial literacy.